(untitled) (Ciudades, 2017)
Massive mobilization of energy and material resources has enabled economic integration among remote areas which were previously autonomous and relatively self-sufficient. Traditional models used for studying the territory on the basis of local resources are no longer effective to describe the new reality. Today the territories have come to serve a global world-system, forgoing their internal complexity and becoming mere infrastructural support of global flows. Faced with the uncertainty that threaten the global system itself, a defensive strategy should focus on preserving those local resources that can provide some flexibility and autonomy to territories.